Estudio de prefactibilidad para la instalación de una planta productora de tabletas de dentífrico - Jara Bravo, Pablo Andres (2022)
The present preliminary study has been made to evaluate the viability of the toothpaste tablets factory implementation. In the first chapter, the current environmental issue related to oral care products is presented and analyzed and the objectives, reach, justification, and hypothesis of the investigation are stated. Moreover, a referential framework composed by journal articles related to our investigation topic and a conceptual framework compounded by the product definition and a group of key words are presented. In the second chapter, the market research is presented. Our objective market is defined and our projected demand from 2020 to 2025 is calculated through the screening of the population and a market survey. In the third chapter, the location of the factory is determined through the Factor Rating Method. The location will be chosen due to workforce, supplies and objective market proximity. In the fourth chapter, the estimation of the appropriate factory extension for the project is presented. It was determined through the analysis of 4 limiting variables: market size, supplies availability, technology capacity and balance point. In the fifth chapter, the product characteristics are detailed, and the process of production is described. It is designed in accordance with the requirements and regulations in force. In the sixth chapter, the structure of the organization is presented. The required work positions and their functions are detailed, and the organization chart is presented. In the seventh chapter, the estimated investment and the costs of production are presented. This data is used to elaborate the operating and financial budget. Then, the economic indicators are calculated, and the analysis of financial ratios and the sensibility of the project is made. Finally, the social evaluation of the project is presented through social indicators and the conclusions and recommendations are exposed.